(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
The Role of Extension Officers in Increasing Rice Production (Case of Siru Village, Lembor District, West Manggarai Regency). Siru Village is one of the villages located in the West Manggarai area, Lembor District. The people of Siru Village are mostly farmers. Siru Village has potential in agriculture, animal husbandry, plantations and freshwater fisheries, which can be developed into a potential sector for the village to develop, in an effort to improve the welfare of the community towards an advanced and independent village. The role of extension workers in increasing rice production in Siru Vilage, Lembor Sub district, West Manggarai Regency is categorized as very instrumental. The role of the instructor as a guide in increasing the production of rice plants obtained a percentage of 55.2% with a very important category. The role of the extension agent as an organizer and dynamist in increasing rice production is 86.8% with a very important category. The role of the extension worker as a technician in increasing rice production is 78.9% with a very important category. The role of the extension agent as a connecting bridge between the research institutions and the farmers got a percentage of 55.2% with a very important category. The role of the extension agent as an educator in increasing rice production is 81.5% with a very important category. The role of extension agents as innovator in increasing rice production has a percentage of 86.8% with a very important category. The role of the extension agent as a facilitator or assistant gets a percentage of 86.8% with a very important category. The role of the extension agent as a consultant in increasing rice production is 86.8% with a very important category. Finally, the role of the extension worker as evaluator gets a percentage of 86.8% with a very important category. Extension workers should do a lot of cooperation with third parties to support the increase in rice production.